2020
DOI: 10.2478/jcbtp-2020-0019
|View full text |Cite
|
Sign up to set email alerts
|

Web-based Financial Reporting Disclosure: Evidence from Selected Banks in the Kingdom of Saudi Arabia (KSA)

Abstract: With insights drawn from legitimacy theory undergirding perceived relative factors expected to influence the level of Web-Based Financial Reporting Disclosure (WBFRD), this paper sheds light on the level of the Web-Based Financial Reporting Disclosure (WBFRD) in selected banks in the KSA in 2017. Several gauges exist for measuring the level of transparency and disclosure practices. As a result of the unique characteristics of the banking sectors operating in the KSA under the Sharia-compliant (Islamic) law, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 20 publications
1
9
1
3
Order By: Relevance
“…These results along with the mean value (3.3551) indicate that updating the web information comes in a moderate level. Investigating the prior results indicated almost similar results (e.g., Sandhu & Singh, 2019;Sarea, 2020) or less (e.g., Çalışkan & Güler, 2014;Pinto & Picoto, 2016). These, results are not acceptable and companies should give the updating process more emphasis in Jordan.…”
Section: Web-based Information Updatingmentioning
confidence: 93%
See 1 more Smart Citation
“…These results along with the mean value (3.3551) indicate that updating the web information comes in a moderate level. Investigating the prior results indicated almost similar results (e.g., Sandhu & Singh, 2019;Sarea, 2020) or less (e.g., Çalışkan & Güler, 2014;Pinto & Picoto, 2016). These, results are not acceptable and companies should give the updating process more emphasis in Jordan.…”
Section: Web-based Information Updatingmentioning
confidence: 93%
“…Therefore, prior studies investigated, for example, the updating frequency of web-based information, communications tools and browsing format. For example, several studies (e.g., Çalışkan & Güler, 2014;Khan, 2016;Pinto & Picoto, 2016;Dolinšek & Lutar-Skerbinjek, 2018;Sandhu & Singh, 2019;Sarea, 2020) found that PDF is the main format for disclosing information on Business and Management Horizons ISSN 2326-0297 2020, Vol. 9, No.…”
Section: Website Presentationmentioning
confidence: 99%
“…The items are based on the literature review and the regulatory framework of the banking system in Paraguay, in line with Resolution N° 65/2010 of the CBP [ 64 ] (see S1 Appendix ). The first 15 items of the IOTCG correspond to mandatory information and analyzes the online information regarding the corporate rules related to the good governance of the bank, such as by-laws and shareholders meetings’ rules or other corporate rules such as Regulations of the Board of Directors [ 47 , 64 , 65 ] as well as information on the bank management such as corporate or Board Structure [ 12 , 19 , 28 , 33 , 38 , 44 , 64 – 66 ]. Likewise, the financial information available on financial statements from the last quarter and historical data are also included in the index according to similar studies and the regulation [ 28 , 40 , 64 , 67 , 68 ].…”
Section: Methodsmentioning
confidence: 99%
“…The first 15 items of the IOTCG correspond to mandatory information and analyzes the online information regarding the corporate rules related to the good governance of the bank, such as by-laws and shareholders meetings’ rules or other corporate rules such as Regulations of the Board of Directors [ 47 , 64 , 65 ] as well as information on the bank management such as corporate or Board Structure [ 12 , 19 , 28 , 33 , 38 , 44 , 64 – 66 ]. Likewise, the financial information available on financial statements from the last quarter and historical data are also included in the index according to similar studies and the regulation [ 28 , 40 , 64 , 67 , 68 ]. Moreover, previous research and regulation state the importance of information transparency concerning minutes of the shareholders’ meetings, dividend distribution policies, and shareholder agreements [ 43 , 64 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation